THE PROFILE OF SMALL COFFEE PRODUCERS IN THE SOUTH OF MINAS GERAIS, BRAZIL - Corsini, Wanêssa Tavares Campos; Corsini, Fábio dos Santos; Naves, Luciana de Paula; Angelocci, Marina Ariente; Paiva, Leandro Carlos; Putti, Fernando Ferrari (Coffee Science - ISSN 1984-3909, 2018)
Highly appreciated by all people worldwide, coffee is a commodity with great economical weight in Brazil. While underscoring analyses on coffee production by the scientific community, current assay deals with the profile of coffee producers in the rural regions of the towns Machado, Poço Fundo and others in the south of the state of Minas Gerais, Brazil. Field work with 225 small producers of the region comprised questionnaires which were analyzed and grouped statistically in discriminating clusters. The correlation of variables was assessed by Pearson´s methodology. Results show that schooling level had a positive correlation with regard to the adequate use of fertilizers and insecticides. Higher schooling level provided greater knowledge on normalizations and correct soil management.